2008
DOI: 10.1177/112972980800900404
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Arteriovenous Fistula Maturation with Intraoperative Blood Flow Measurements

Abstract: Intraoperative blood flow measurements obtained at the time of autologous AVF construction can identify fistulas that are unlikely to mature; and therefore, that require immediate revision or abandonment which will ultimately expedite the establishment of a useful access in the HD patient. This is the first study to establish the minimal flow values uniquely needed for both radial artery and brachial artery AVFs to expect primary maturation to a functional access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 14 publications
1
17
0
3
Order By: Relevance
“…Several strategies to increase the AVF maturation rate have been proposed. These include preoperative and intraoperative examinations to identify fistulas at risk of maturation failure and aggressive postoperative interventions to salvage nonmaturing fistulas (5)(6)(7)(8). Nonetheless, less attention has been paid to the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies to increase the AVF maturation rate have been proposed. These include preoperative and intraoperative examinations to identify fistulas at risk of maturation failure and aggressive postoperative interventions to salvage nonmaturing fistulas (5)(6)(7)(8). Nonetheless, less attention has been paid to the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Another report by Won et al [14] found that a radiocephalic AVF flow less than 160 mL/min was associated with a high early failure rate, and intraoperative low flow was determined to be an independent risk factor. A report by Berman et al [15] was the first study to establish the minimal flow rates needed for maturation and subsequent patency of brachiocephalic AVF. According to the report of Berman et al [15], a cutoff of 308 mL/min was needed for Glomerulonephritis, unknown kidney disease, and polycystic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…[21] observed during the 12-month period in 70 autologous AVFs intraoperative blood flow measurements at the time of autologous AVF construction can identify fistulas that are unlikely to mature; and therefore, that require immediate revision or abandonment which will ultimately expedite the establishment of a useful access in the HD patient.…”
Section: Discussionmentioning
confidence: 99%